Working Creatively Across Media, Language and Location: East Africa–UK Literary Collaborations. Issue 1 (2nd January 2021) - Wallis, Kate
Abstract : In 2016, the British Council launched their annual new Art new Audiences (nAnA) grant programme — an open call for cultural producers in East Africa and the UK to apply for up to £30, 000 to collaboratively create. This interview piece shares a series of conversations with literary producers from three nAnA-funded projects — all of which brought together writers and visual artists in East Africa and experimented with visual, sonic, and textual forms. I begin by talking to Ugandan poet and zine-maker Gloria Kiconco, about her work on 'Zine Futures' awarded a nAnA grant in 2016. This project was conceived by Sarita Mamseri (Founder of Bookstop Sanaa), and worked with artists in Kampala and Dar es Salaam to explore the creative possibilities of the zine form through workshops and exhibitions. Eligibility for the nAnA grants necessitated forming partnerships between a UK-based individual or organisation, and individuals or organisations in two East African countries (the programme was expanded in 2019 to applications from creative producers in West and Southern Africa). The second interview explores a publishing collaboration I was directly involved in as co-director of Kigali-based Huza Press, when, in 2017, we were awarded a grant to create multimedia imprint 'RadioBook Rwanda'; I speak to lead collaborators Louise Umutoni, Director of Kigali-based Huza Press; Lily Green, Director of Bristol-based No Bindings; and Otieno Owino, formerly Editor at Nairobi-based Kwani Trust. 'RadioBook Rwanda' produced three beautiful pocketbook editions which set new short stories in English and Kinyarwanda by Rwandan writers – Mutsinzi Eric, Annick La Reine Shimwa and Jimmy Tuyiringire – in conversation with artwork from Kenya's Nduta Kariuki and Jess Atieno, and Rwanda's Souls. Each of the three pocketbooks came with an invitation to dive into their universe not only through their pages but through a podcast built around each book's themes: from relationships to modern myths to resistance. The final conversation is with London-based Somali poet Sumia Jaama who founded Sawti — a literary project aimed at exploring and showcasing linguistic and cultural diversity evident across East African storytelling on the continent and within the diaspora. Awarded a nAnA grant in 2018, Jaama worked with collaborators across the UK, Tanzania, and Sudan to produce workshops and a film, as well as launching a new multilingual poetry prize and zine. The nAnA grant model deliberately tries to move away from forcing individual UK and Africa-based artists to co-create, instead allowing scope for different models of collective cultural production. The range of exciting work that has come out of this – from the Jalada Mobile Literary and Arts Festival, to No Hats No Hoods Records' 'Ethiopiyawi Meets Grime' collaboration with Ethiopian Records – is testament to its success. However, unsurprisingly, given the toxic and unjust legacy of British colonial violence, this interview series makes visible particular pressure points created through a funding model that enables innovative East African literary production but only through a relationship with the UK. While reflective of these complexities, and those of working within and across multiple media, languages, and locations, this series of conversations, which took place between Zoom and email over the first half of 2020, is ultimately richly affirming of the creative possibilities for independent publishers and literary initiatives working collaboratively.